Headteachers' views on inclusion: an exploration using Q-methodology - Frater, Matthew (2021)
Despite the UK’s Department for Education and Department of Health (2015) pledging a commitment to inclusion within the SEND Code of Practice, statistics indicate there has been a rise in the number of children being educated within specialist settings over recent years (Department for Education, 2020). Understandably, then, inclusion continues to receive a high level of national attention, with an argument being made by the House of Commons Education Committee (2018, 2019) that not enough is currently being done to promote inclusive education. There are a number of professional roles that are influential in the facilitation and development of inclusive education – arguably one of the most important of these roles being that of the headteacher (Billingsley et al., 2018; Rapp, 2010). Research has identified, for example, that headteachers' viewpoints on inclusion can impact upon their decision making and behaviour which in turn impacts directly and indirectly upon the implementation of inclusive practices within their settings (Causton et al., 2013; Hoppey & McLeskey, 2013; Meo, 2015). It is argued in the present research, that in order to understand the likely development of inclusive practice in UK schools going forward - and indeed, in order to effectively influence such practice - it is imperative that a more detailed understanding is gained of UK headteachers’ current viewpoints on inclusion (Billingsley et al., 2018; Rapp, 2010 Burstein et al., 2004; Shani & Koss, 2015). A Q-methodological approach was adopted to explore and identify the range of viewpoints held in relation to inclusion within a sample of twenty mainstream headteachers. A by-person factor analysis was completed, revealing two detailed viewpoints: Viewpoint One – A pragmatic approach to inclusion and a belief that under current circumstances a segregated system of education is more suited to meeting the needs of all learners’ Viewpoint Two - Inclusion is a right which is achievable through a positive school culture and by working together The viewpoints were distinct and had significant differences in the way that participants holding the viewpoints evaluated some aspects of inclusion. The key difference between the viewpoints was the extent to which participants perceived that mainstream schools presently can or even should cater for all students, though other more subtle differences were also apparent. Some significant areas of consensus across the viewpoints were also revealed however - for example, around the importance of school culture and systemic collaboration for the success of inclusion. The areas of contention and of agreement revealed through the research - discussed here in detail and in relation to existing literature - will be useful to those seeking to develop inclusion-related educational policy, and to those seeking to further inclusive practice in schools. Policy makers and educational psychologists may wish to consider if a one-size-fits all approach towards promoting inclusion is likely to be successful given the findings. A number of implications for professional practice and research are identified and explored including; how policymakers and local authorities may wish to clarify the concept of inclusion and their expectations, and how educational psychologists may support the development of positive systemic relationships and collaboration.